Risk of radiologic examinations during pregnancy. - Ramos, H V (Acta Médica Portuguesa, 1996)
Considering that there's a lack of information concerning the risks of radiation exposure in pregnancy, the author identifies such risks and estimates its magnitude. He underlines the fact that radiological examinations deliver lower doses in relation to those that can be proved to be malefic to the embryo, both in the somatic and genetic plan.